Complementary bimodal approach to monitoring of photodynamic therapy with targeted nanoconstructs: numerical simulations. (January 2019) - Kirillin, M.Yu.; Kurakina, D.A.; Perekatova, V.V.; Orlova, A.G.; Sergeeva, E.A.; Khilov, A.V.; Subochev, P.V.; Turchin, I.V.; Mallidi, S.; Hasan, T.
Abstract: We propose a new approach to monitoring photodynamic therapy (PDT) of glioblastoma with the use of targeted nanoconstructs containing a photosensitiser (PS) [benzoporphyrin derivative (BPD)] and IRDye800 dye, antibodies for efficient accumulation of the drug in a tumour, and a chemotherapeutic agent for combined effect on tumour cells. Application of IRDye800 is determined by the shift of its absorption and fluorescence spectra to the near-IR range with respect to BPD that ensures a higher imaging depth. Monitoring of PDT is based on the simultaneous fluorescence and optoacoustic (OA) imaging. Fluorescence imaging provides visualisation of fluorescence agents with high molecular sensitivity and monitoring of the effectiveness of PDT by PS photobleaching. OA allows one to examine the vascular pattern of the tumour environment, as well as assess the depth of the tumour. IRDye800 is a better contrast agent in comparison to BPD due to red-shifted spectral characteristics and a higher fluorescence quantum yield. Monte Carlo simulations combined for OA simulations with K-wave modelling allowed the feasibility of the complementary approach to be studied and demonstrated that this combination allows one to localise a tumour with a size of 2 mm at depths from 100 μm to 2 mm.